Psychometric Testing of an Indonesian-Version Diabetes Self-Management Instrument - RAHAYU, Henik Tri (J Nurs Res, 2020)
BACKGROUND: Self-management is one of the vital elements in diabetes management for adults with Type 2 diabetes mellitus (T2DM). Although the number of people with T2DM in Indonesia has risen, clinical understanding of the problems related to practicing diabetes self-management (DSM) is limited because of the lack of a valid measurement instrument. The 35-item Diabetes Self-Management Instrument (DSMI-35) is one instrument widely used in research to assess DSM-related behavior among patients with diabetes. PURPOSE: This study was designed to translate the psychometric properties of the Indonesian version of the DSMI-35 and evaluate the efficacy of this instrument in a sample of Indonesian adults with T2DM. METHODS: Forward and backward translation processes were used to translate the DSMI-35 into Indonesian (IDN-DSMI). Then, the translation equivalence, content validity, face validity, construct validity, and internal consistency were assessed using a sample of 222 Indonesian adults with T2DM from eight public health centers. Confirmatory factor analysis was used to test the data. RESULTS: The confirmatory factor analysis confirmed that the 35 items all had acceptable goodness of fit. Although the analysis supported removing several of the items, removal of these items was not theoretically justified. The average variance extracted was acceptable, and composite reliability was satisfied. The Cronbach's alpha was .96 for the IDN-DSMI and .84–.93 for the subscales. The significant interitem correlations between some items were consistent with the findings of other previous studies. CONCLUSIONS/IMPLICATIONS FOR PRACTICE: The IDN-DSMI is a valid and reliable instrument that may be used to measure DSM behavior in Indonesian patients with T2DM in primary healthcare settings.